The bridge over the racial divide : rising inequality and coalition politics - Wilson, William J., 1935- (University of California Press, 1999)
Studies the rising inequality in American society and addresses the need for a progressive, multiracial political coalition to combat that inequality.
Keywords: United States -- Race relations -- Political aspects.; Racism -- Political aspects -- United States.; Coalitions.; African Americans -- Politics and government.; African Americans -- Social conditions -- 1975-; Minorities -- Political activity -- United States.; Minorities -- United States -- Social conditions.; Social classes -- Political activity -- United States.; États-Unis -- Relations raciales -- Aspect politique.; Racisme -- Aspect politique -- États-Unis.; Noirs américains -- Politique et gouvernement.; Noirs américains -- Conditions sociales -- 1975-; Minorités -- Activité politique -- États-Unis.; Classes sociales -- Activité politique -- États-Unis.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; African Americans -- Politics and government; African Americans -- Social conditions; Coalitions; Minorities -- Political activity; Minorities -- Social conditions; Race relations -- Political aspects; Racism -- Political aspects; Social classes -- Political activity; United States; Ethnische Beziehungen; Sozialstruktur; USA; Etnische betrekkingen.; Ongelijkheid.; Politieke aspecten.; Verenigde Staten.; Since 1975